Potentially Habitable Terrestrial Exoplanets based on the Habitability Index for Transiting Exoplanets (HITE) Value - Rozzykin, Achmad Zainur; Lomban, Claudia Amelia; Ikhsan, Muhammad Isnaenda (BRIN Publishing, 2025)
In-depth exploration of exoplanet habitability involves a crucial screening processto identify a subset with the potential for sustaining life. The Habitability Index for TransitingExoplanets (HITE) emerges as a vital tool, quantifying a planet’s habitability byassessing the probability of it having a solid surface and liquid water. Represented bythe symbol H, the index assigns values on a scale from 0 to 1. The closer the value to 1,the greater the potential for habitability. H integrates parameters derived from transitdata, encompassing orbital period, transit depth, duration, surface gravity, radius, andeffective temperature of the host star. Through the Virtual Planetary Laboratory (VPL),the calculation of H is executed for exoplanets with terrestrial mass (0.3–10 M⊕) sourcedfrom the Transiting Exoplanet Survey Satellite (TESS) and K2 missions. The results showthat the exoplanets with the highest H values are TOI-700 d from TESS, with a value of0.95202. Of the 228 planets examined, around 9.21% are identified as potentially habitable.